Facile, one-pot, in aqua synthesis of catalytically competent gold nanoparticles using pyrogallol[4]arene as the sole reagent. Issue 44 (14th May 2019) - Adhikari, Laxmi; Larm, Nathaniel E.; Wagle, Durgesh V.; Atwood, Jerry L.; Baker, Gary A.
Abstract : Rapid and facile synthesis of macrocycle-capped gold nanoparticles employing pyrogallol[4]arenes as a dual-role reducing and stabilizing agent. Abstract : We report a simple, single-pot, room temperature synthetic route to prepare colloidally-stable pyrogallol[4]arene-capped gold nanoparticles. The number of carbon atoms in the pyrogallol[4]arene pendent alkyl chain and the addition of base ( e.g., NaOH) are both found to significantly impact the resulting colloid size, stability, and catalytic activity for nitroarene reduction.